Eat Walk Engage: Enabling acute care teams to deliver consistent fundamentals of care for older people. (21st July 2022) - Cahill, Margaret; Neill, Sharne; Treleaven, Elise; Lee‐Steere, Karen; Carter, Andy; McCormack, Linda; Mudge, Alison
Abstract: Aims: Fundamentals of care are particularly important for older people in acute inpatient settings, who are at increased risk of serious hospital‐associated complications like delirium and functional decline. These complications occur due to interactions between clinical complexity and the complex processes and context of hospital care and can be reduced by consistent attention to the fundamentals of care. This paper aims to illustrate of how multi‐level nursing leadership of fundamentals of care can be supported to emerge within complex multidisciplinary delivery systems in acute care. Design: Discussion paper informed by clinical and organizational experience of a multidisciplinary leadership team and complexity leadership theory. Data sources: We provide a series of vignettes as practical illustrations of a successful multidisciplinary improvement program called Eat Walk Engage which supports the delivery of better care for older inpatients, significantly reducing delirium. We argue that taking a broader complexity‐based approach including collaborative multidisciplinary engagement, iterative and integrated interventions and appropriate knowledge translation frameworks can enable emergent leadership by nurses at all levels. Implications for nursing: This promising approach to improving care for older patients requires organizational support for facilitation and reflective practice, and for meaningful data to support change. Our discussion challenges nursing leaders to support the time, agency and connections their nursing staff need in order to emerge as local leaders in fundamental care. Conclusion: The debate around scope and responsibilities for fundamentals of care in hospital care has important practical implications for conceptualizing leadership and accountability for improvement. Impact: Our discussion illustrates how a structured multidisciplinary approach that acknowledges and navigates complexity can empower nurses to lead and improve outcomes of older patients in acute care.